A land of permanent goodbyes - Abawi, Atia (Philomel Books, 2018)
After their home in Syria is bombed, Tareq, his father, and his younger sister seek refuge, first with extended family in Raqqa, a stronghold for the militant group, Daesh, and then abroad. Tareq lives with his big and loving family... until the bombs strike. The city is in ruins, and in the wake of destruction, he's threatened by Daesh fighters and witnesses a public beheading. Tareq's family knows that to continue to stay alive, they must leave. As they travel as refugees from Syria to Turkey to Greece, facing danger at every turn, Tareq must find the resilience and courage to complete his harrowing journey.